Parameter‐based assessment of disturbed and intact components of visual attention in children with developmental dyslexia. Issue 5 (27th February 2014) - Bogon, Johanna; Finke, Kathrin; Schulte‐Körne, Gerd; Müller, Hermann J.; Schneider, Werner X.; Stenneken, Prisca
Abstract People with developmental dyslexia (DD) have been shown to be impaired in tasks that require the processing of multiple visual elements in parallel. It has been suggested that this deficit originates from disturbed visual attentional functions. The parameter‐based assessment of visual attention based on Bundesen's (1990) theory of visual attention allows one to identify and quantify the underlying deficits. The present study provides the first groupwise comparison between children with DD (n = 12; mean age 9.84 years) and typically developing children (n = 12; mean age 9.87 years) with regard to intact and disturbed components of visual attention. From the performance on whole‐ and partial‐report tasks, we derived individual parameter estimates of four different parameters: visual processing speed, storage capacity of visual short‐term memory (VSTM), laterality of attentional weighting and efficiency of top‐down control. Groupwise comparisons revealed that general attentional resources, processing speed and VSTM storage capacity, are impaired in children with DD compared to typically developing children. In contrast, selectivity parameters, laterality of attentional selection and attentional top‐down control did not differ between these groups. Relating the current findings to previous results, obtained in highly comparable methodological settings, from single cases of children with DD, and from a group of adults with DD, we conclude that slowed perceptual processing speed is a primary visual attentional deficit in DD. Furthermore, reduced VSTM storage capacity seems to modulate the difficulties in written language processing imposed by the disorder.